Excavations at Tall Jawa, Jordan - Daviau, Michèle, author.
1 online resource
Keywords: In Excavations at Tall Jawa, Jordan: Volume 3, The Iron Age Pottery , Michèle Daviau presents a detailed typology of the Iron Age pottery excavated from 1989 to 1995. She looks beyond the formal changes to an in-depth analysis of the forming techniques employed to make each type of vessel from bowls to colanders, cooking pots to pithoi. The changes in fabric composition from Iron I to Iron II were more significant than those from Iron IIB to IIC, although changes in surface treatment, especially slip color, were noticeable. Petrographic analysis of Iron I pottery by Stanley Klassen contributes to our growing corpus of fabric types, while Peter Epler documents typical Ammonite painted patterns and Elaine Kirby and Marianne Kraft present a typology of potters’ marks.